Targeting Smoking Triggers: A Nurse-led Intervention for Tobacco Smoking Cessation - Sadeq Al-Fayyadh; Ali Hussein Alek Al-Ganmi; Musaab Majid Abdulwahhab; Shaymaa Mohammed Hussein; Linda Cook; Abdulellah Al-Solais; Mayada Sabri (Nurse Media Journal of Nursing, 2022)
Background: Nursing interventions tailored to the smoking triggers in patients with non-communicable chronic diseases are essential. However, these interventions are scant due to the nature of factors associated with smoking cessation and the poor understanding of the effect of nurse-led intervention in Iraq.Purpose: This study aimed to determine the dominant smoking triggers and examine the effects of a tailored nursing intervention on smoking behavior in patients with non-communicable chronic diseases.Methods: Convenience samples of 128 patients with non-communicable chronic diseases, male and female patients, who were 18-70 years old, were recruited in this quasi-experimental, randomized comparative trial in the outpatient clinic in one major teaching hospital in Baghdad City, Iraq. The intervention included simple yet specific instructions that were given both orally and in written form to the study samples to enable them to manage their craving to smoke for 6 weeks. The smoking triggers were assessed using Why Do You Smoke questionnaire. Participants were randomly allocated to receive either the nurse-led intervention or standard care. Data were analyzed using descriptive statistics, independent sample t-tests, logistic regression, and two-sided tests.Results: Stress reduction was the dominant smoking trigger among subjects. The percentage of participants who were either able to completely quit smoking or reduce the number of smoked cigarettes per day (n=19, 29.7%; n=28, 43.8%, respectively) was greater in the study group than those in the control group (n=5, 5.8%; n=5, 5.8%, respectively). Study findings demonstrated significant differences in the inability to improve readiness to quit smoking between the intervention group and control group (p=0.000) at the sixth-week follow-up.Conclusion: The tailored nursing intervention was effective for a successful achievement of smoking reduction and cessation among patients with non-communicable chronic diseases, and a potential to equip nurses in clinical settings to support patients to achieve this is recommended.